Ab initio DFT study of ideal shear strength of polytypes of silicon carbide - Umeno, Y.; Kinoshita, Y.; Kitamura, T. (Проблемы прочности, 2008)
Ab initio density functional calculations are performed to investigate the ideal shear deformation of SiC poly types (3C, 2H, 4H, and 6H). The deformation of the cubic and the hexagonal poly types in small strain region can be well represented by the elastic properties of component Si4C-tetrahedrons. The stacking pattern in the polytypes affects strain localization, which is correlated with the generalized stacking fault (GSF) energy profile of each shuffle-set plane, and the ideal shear strength. Compressive hydrostatic stress decreases the ideal shear strength, which is in contrast with the behavior of metals.